Double skin façade integrating semi-transparent photovoltaics: Experimental study on forced convection and heat recovery. (15th November 2020) - Ioannidis, Zisis; Rounis, Efstratios-Dimitrios; Athienitis, Andreas; Stathopoulos, Ted
Highlights: Experimental setup and analysis of DSF integrating STPV. Nusselt number coefficient correlations development for DSF integrating STPV. Dimensionless number in the Nusselt number coefficients. Introduction of a Heat recovery index, different from the thermal efficiency. Abstract: Semi-Transparent Photovoltaics (STPV) can be integrated on Double Skin Facades (DSF) to enhance the energy performance of a building. The integrated STPV can simultaneously control solar gains and generate electricity. The optimal operation of the DSF through control of the air flow can enhance the heat extraction from the DSF during heating season, increase the electrical and thermal efficiency of the system, and decrease the heating load of the building. In the present study, the lack of literature in the development of an average Nusselt number correlations for DSF integrating STPV (DSF-STPV) is identified and a new index which corresponds to the heat that is recovered is introduced and is distinguished from the thermal efficiency of the system. Also, in the present study, average Nusselt number correlations for air flow in DSF with STPV are experimentally developed, using a full-scale outdoor test facility. The effect of the incident solar radiation, the wind driven exterior convection and the ambient temperature have been taken into consideration in the development of these convective heat transfer correlations. The properties of the materials of the DSF are also taken into consideration such as the transmittance of the STPV, the PV cell efficiency and the thermal conductance of the glazing. In this process, a new dimensionless number is defined to generalize the results, particularly for the expected operating conditions. The Nusselt number correlations are then used for a sensitivity analysis for different wind speeds and for the assessment of the thermal performance of the system. The heat losses of a typical building in comparison to a building that integrates DSF-STPV can be 20% higher resulting in losses that reach values of 8 W/m 2 of façade area. The heat recovery index can reach more than 30% and the total solar utilization efficiency can be between 30% and 77% for different experimental conditions.